Corticosteroids for the common cold. - Hayward, G; Thompson, M; Perera, R; Mar, D; Glasziou, P; Heneghan, C (2012)
The common cold is a frequent illness, which, although benign and self-limiting, results in many consultations to primary care and considerable loss of school or work days. Current symptomatic treatments have limited benefit. Corticosteroids are an effective treatment in other upper respiratory tract infections and their anti-inflammatory effects may also be beneficial in the common cold. To compare corticosteroids versus usual care for the common cold on clinical response rates in children and adults. We searched the Cochrane Central Register of Controlled Trials (CENTRAL) 2012, Issue 5 which includes the Acute Respiratory Infections (ARI) Group's Specialised Register, the Database of Reviews of Effects (DARE) 2012, Issue 4 and the NHS Health Economics Database 2012, Issue 5; MEDLINE (1948 to May week 2, 2012) and EMBASE (January 2010 to May 2012). Randomised, double-blind, controlled trials comparing corticosteroids to placebo or to standard clinical management. Two review authors independently extracted data and assessed trial quality. We were unable to perform meta-analysis and instead analysed results using narrative description of the available evidence. We included two trials (253 participants). Both compared intranasal corticosteroids to placebo; no trials studied oral corticosteroids. No benefit of intranasal corticosteroids was demonstrated for duration or severity of symptoms. In one trial of 54 participants, the number of symptomatic days was 10.3 in the placebo group, compared to 10.7 in those using intranasal corticosteroids (P = 0.72). A second trial of 199 participants reported no significant differences in duration of symptoms. There were no differences reported in terms of: adverse events; complications (one case of sinusitis, one case of acute otitis media, both in corticosteroid groups); presence of rhinovirus in nasal aspirates; or treatment for secondary infections. Neither trial reported our primary outcome measure of percentage of participants with resolution at different time points. A lack of comparable outcome measures meant we were unable to combine the data. Current evidence does not support the use of intranasal corticosteroids for symptomatic relief from the common cold. However, there were only two trials and limited statistical power. Further large randomised placebo-controlled trials in adults and children are required to answer this question.